Terrorism Risks for Bridges in a Multi-Hazard Environment. Issue 3 (September 2014) - Stewart, Mark G.; Mueller, John
The paper will assess terrorist threats to new and existing bridges and the cost-effectiveness of protective counter-terrorism measures. This analysis will consider threat likelihood, cost of security measures, risk reduction and expected losses to compare the costs and benefits of protective measures to bridges to decide which protective measures are cost-effective. In this paper, a break-even cost-benefit analysis determines the minimum probability of an attack, absent the protective measures, that is required for the benefit of the protective measures to equal their cost for new and existing bridges. It was found that unless terrorist threat probabilities are high, then typical protective measures are not cost-effective. Bridges and other critical infrastructure are subject to a range of natural and man-made hazards, and terrorism is most likely not as important a threat as natural hazards. It was found that economic risks to bridges from floods, earthquakes, and ship impact are higher than threats from terrorism.